2010
DOI: 10.4319/lo.2010.55.3.0973
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of warming effects on phytoplankton productivity rates and their dependence on eutrophication status

Abstract: Using 31-yr data from measurements in a lake that has experienced change in eutrophication status, I showed that the effects of global warming on chlorophyll a (Chl a)-normalized maximum rates of photosynthesis (P max : Chl a) may be positive, nonsignificant, or negative, depending on nutrient availability. The magnitude of P max : Chl a change in response to warming showed hyperbolic relationships with phosphorus concentrations; it was positive and constant when total phosphorus (TP) in the lake water exceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 28 publications
8
39
1
Order By: Relevance
“…By that time, the winter overturn of the water column was weaker in response to warmer winters (Jacquet et al 2005). Furthermore, the increase of the summer temperature stimulates primary production (Tadonléké 2010), whereas the longer stratification promotes the appearance of large, filamentous phytoplankton in Lake Bourget (Jacquet et al 2005). Biologically mediated consequences of climate warming hence also contribute to increase OM fluxes to the sediment and, in turn, respiration.…”
Section: Discussionmentioning
confidence: 99%
“…By that time, the winter overturn of the water column was weaker in response to warmer winters (Jacquet et al 2005). Furthermore, the increase of the summer temperature stimulates primary production (Tadonléké 2010), whereas the longer stratification promotes the appearance of large, filamentous phytoplankton in Lake Bourget (Jacquet et al 2005). Biologically mediated consequences of climate warming hence also contribute to increase OM fluxes to the sediment and, in turn, respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the GDD model, there was a positive relationship between chlorophyll a values and mean length of age-0 walleye. Both the GDD metric and chlorophyll a could be an index of lake productivity and phytoplankton biomass, as increased phytoplankton biomass has been associated with warming temperatures under eutrophic conditions (Tadonleke, 2010). Increased growth rates of age-0 walleye associated with increased chlorophyll a concentrations could also be a result of bottom-up trophic interactions as increases in productivity at the bottom of the food chain could resonate up through the food chain and generate greater prey availability to age-0 walleye (McQueen et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the response to water temperature was positive in primary production and negative in respiration, but this response depended of the nutrient availability, since the metabolic processes is dependent on many factors (Tadonléke, 2010). Tonetta et al (2013) have also demonstrated that changes in water temperature and nutrient availability drive temporal variation in phytoplankton in Peri Lake.…”
Section: Temporal Variationmentioning
confidence: 99%
“…Phytoplankton productivity is sensitive to nutrient, especially phosphorus availability (Tadonléke, 2010;Kerimoglu et al, 2013). Phosphorus enrichment and light availability sustain the pelagic chlorophyll a and primary production, while in oligotrophic lakes phytoplanktonic growth and production are frequently constrained by nutrient limitation (Carpenter et al, 2001;Liboriussen and Jeppesen, 2003).…”
Section: Introductionmentioning
confidence: 99%